Circ_0002984 induces proliferation, migration and inflammation response of VSMCs induced by ox‐LDL through miR‑326‐3p/VAMP3 axis in atherosclerosis. Issue 16 (25th June 2021) - Li, Ruogu; Jiang, Qiliang; Zheng, Yue
Abstract: Atherosclerosis can result in multiple cardiovascular diseases. Circular RNAs (CircRNAs) have been reported as significant non‐coding RNAs in atherosclerosis progression. Dysfunction of vascular smooth muscle cells (VSMCs) is involved in atherosclerosis. However, up to now, the effect of circ_0002984 in atherosclerosis is still unknown. Currently, we aimed to investigate the function of circ_0002984 in VSMCs incubated by oxidized low‐density lipoprotein (ox‐LDL). Firstly, our findings indicated that the expression levels of circ_0002984 were significantly up‐regulated in the serum of atherosclerosis patients and ox‐LDL‐incubated VSMCs. Loss of circ_0002984 suppressed VSMC viability, cell cycle distribution and migration capacity. Then, we carried out ELISA assay to determine TNF‐α and IL‐6 levels. The data implied that lack of circ_0002984 obviously repressed ox‐LDL–stimulated VSMC inflammation. Meanwhile, miR‐326‐3p, which was predicted as a target of circ_0002984, was obviously down‐regulated in VSMCs treated by ox‐LDL. Additionally, after overexpression circ_0002984 in VSMCs, a decrease in miR‐326‐3p was observed. Subsequently, miR‐326‐3p was demonstrated to target vesicle‐associated membrane protein 3 (VAMP3). Therefore, we hypothesized that circ_0002984 could modulate expression of VAMP3 through sponging miR‐326‐3p. Furthermore, we confirmed that up‐regulation of miR‐326‐3p rescued the circ_0002984 overexpressing‐mediated effects on VMSC viability, migration and inflammation. Additionally, miR‐326‐3p inhibitor‐mediated functions on VSMCs were reversed by knockdown of VAMP3. In conclusion, circ_0002984 mediated cell proliferation, migration and inflammation through modulating miR‐326‐3p and VAMP3 in VSMCs, which suggested that circ_0002984 might hold great promise as a therapeutic strategy for atherosclerosis.